M-Learning Adoption: A Perspective from a Developing Country - Iqbal, Shakeel; Qureshi, Ijaz A. (International Review of Research in Open and Distributed Learning, 2012)
M-learning is the style of learning for the new millennium. Decreases in cost and increases in capabilities of mobile devices have made this medium attractive for the dissemination of knowledge. Mobile engineers, software developers, and educationists represent the supply side of this technology, whereas students represent the demand side. In order to further develop and improve this medium of learning it is imperative to find out students’ perceptions about m-learning adoption. To achieve this objective a survey was conducted among the students of 10 chartered universities operating in the twin cities of Rawalpindi and Islamabad in Pakistan. The results indicate that perceived usefulness, ease of use, and facilitating conditions significantly affect the students’ intention to adopt m-learning, whereas perceived playfulness is found to have less influence. Social influence is found to have a negative impact on adoption of m-learning. The findings of this study are useful in providing guidance to developers and educators for designing m-learning courses specifically in the context of developing countries.